Low-dose subconjunctival bevacizumab to augment trabeculectomy for glaucoma - Sedghipour MR (Dove Medical Press, 2011)
Mohammad-Reza Sedghipour, Ali Mostafaei, Yousef TaghaviNikoukari Ophthalmology University Hospital, Tabriz University of Medical Sciences, Tabriz, IranBackground: The purpose of this study was to assess the effect of bevacizumab in maintaining intraocular pressure lowered by trabeculectomy in refractory open-angle glaucoma.Methods: Thirty-seven eyes from 37 patients referring to Nikoukari Ophthalmology University Hospital in Tabriz were enrolled in this randomized clinical trial. Seventeen patients were randomly assigned to receive bevacizumab augmentation after trabeculectomy, and 20 patients were assigned to a control group receiving a placebo injection of normal saline. Bevacizumab was injected subconjunctivally at a dose of 0.2 mg. Intraocular pressure was measured on eight occasions, ie, at baseline, 24 hours, 3 days, 7 days, 2 weeks, 1 month, 2 months, and 3 months after treatment.Results: Men constituted 81% of the participants, who were of mean age 67.5 years. Twenty-nine patients had secondary open-angle glaucoma, while eight patients had primary open-angle glaucoma. Intraocular pressure decreased from a mean of 28.4 mmHg at baseline to a mean of 12.1 mmHg during the first day and to 15.1 mmHg after 3 months. Adding bevacizumab to trabeculectomy was not found to affect intraocular pressure differently to placebo. Neither the results of repeated measurements analysis nor single comparison statistical tests were significant for a difference in efficacy of bevacizumab versus placebo.Conclusion: Subconjunctival bevacizumab 0.2 mg was not found to affect the trend in intraocular pressure more than placebo after trabeculectomy for open-angle glaucoma.Keywords: glaucoma, trabeculectomy, bevacizumab, antivascular endothelial growth factor agents